Hygiene and Sanitation at Bubur Harisah in Gresik Regency - Mochamad Rizal Maulana (Universitas Airlangga, 2018)
Food is a basic human need that must be fulfilled every day. Food preparation and serving should be done with appropriate processing so that the food can be utilized by the human body. Bubur Harisah is a special food of Gresik Regency which be sought after by people because of its health benefits. The research was conducted to identify the condition of hygiene and sanitation and the quality of Eschericia coli bacteria in bubur harisah based on Permenkes RI Nomor 1096 Tahun 2011 tentang Higiene Sanitasi Jasaboga. The research was done by observational method and cross sectional research design. The sample of the research was taken by non probability as 8 porridge harisah seller in Gresik Regency. Data collection was done by filling out questionnaires, observations, and laboratory tests. The result of the assessment of the hygiene and sanitation condition in bubur harisah that there are 4 sellers (50%) who did not fulfill the test of physical condition of hygiene and sanitation with percentage below 93%. There is 1 seller (12.5%) with positive sample test of bacteria Escherichia coli. Observation results test of physical condition show that condition of hygiene and sanitation of porridge harisah have not fulfill standard. The conclusion of this study is that there was bacteria Escherichia coli in the sample of bubur harisah. The suggestion for this research is that food traders should improve hygiene and sanitation conditions and conduct food handler training which is further supervised and supervised by the health office of Gresik Regency.